The role of CO2 on respiration and metabolism during hypercapnic and normocapnic recovery from exercise - Tsakiris, T. S.; Konstantopoulos, A. I.; Bourdas, D. I. (Research Quarterly for Exercise and Sport, 2021)
High intensity exercise can lead to depletion of CO2 from the body (hypocapnia). This disturbance becomes more noticeable during recovery or between seasons of intermittent exercise, putting the subject in a neural fatigue state.